2012
DOI: 10.5296/ast.v1i1.2980
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Relationships of Twenty-One Nereids Species Inferring Two Different Evolutionary Origins?

Abstract: Fragments of mitochondrial cytochrome c oxidase subunit I (COI) gene of 21 nereids species were collected and compared to investigate the systematic and evolution of Nereididae. Total of 599 base pair (bp) nucleotide sequences revealed 285 polymorphic sites. Forty-nine variable sites were found in the corresponding 199 amino acid fragments. Phylogeny was constructed based on neighbor-joining (NJ) and maximum likelihood (ML) methods. Two shallow evolutionary clades were found, which were associated with the mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…Perinereis is considered a non-monophyletic genus (Bakken & Wilson, 2005; Glasby et al ., 2013; Liu et al ., 2013). The presence of transverse bars on area VI, or more restrictively smooth bars as stated in subsequent studies (Hutchings et al ., 1991; Bakken et al ., 2009), has been traditionally regarded as the main feature to recognize Perinereis species (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Perinereis is considered a non-monophyletic genus (Bakken & Wilson, 2005; Glasby et al ., 2013; Liu et al ., 2013). The presence of transverse bars on area VI, or more restrictively smooth bars as stated in subsequent studies (Hutchings et al ., 1991; Bakken et al ., 2009), has been traditionally regarded as the main feature to recognize Perinereis species (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Liu, Liu, Wang, Guan, and Ge (), to the best of our knowledge, is the only attempt to use molecular tools to evaluate phylogenetic relationships of Nereididae and suggested that the family is paraphyletic. This study included 22 species in eight genera and used only one marker (Cytochrome c Oxidase subunit 1).…”
Section: Introductionmentioning
confidence: 99%
“… 2011 ; Liu et al. 2012 ; Nygren 2014 ; Weigert et al. 2016 ; Weigert and Bleidorn 2016 ; Alves et al.…”
unclassified
“…The importance of the application of molecular data to study this family has been recently evidenced in two studies that revealed the paraphyletic status of two traditionally recognized morphological subfamilies (Nereidinae and Gymnonereidinae) (Liu et al. 2012 ; Alves et al. 2020 ).…”
mentioning
confidence: 99%